Debt Relief for the Poorest : an OED Review of the HIPC Initiative. - Gautam, Madhur, 1960- (World Bank e-Library., 2003)
The Heavily Indebted Poor Countries (HIPC) Debt Initiative was designed to relieve the high external debt of some of the world's poorest nations. The Initiative was put in place by the World Bank and the International Monetary Fund (IMF) in 1996 and enhanced in 1999. The HIPC Debt Initiative addresses a key obstacle to economic growth and poverty reduction, but it also contains multiple and overly-ambitious objectives. This work is an independent evaluation which assesses the progress and prospects of the HIPC Debt Initiative achieving its objectives.